A study on impact of fess in the outcome of management of active mucosal type of CSOM - Sachithanandam, Suresh kumar; Sankaralingam, Ganapathy; Chellakani, Ravikumar; Chinnadurai, Karuppasamy; Palaramakrishnan, Rajeswari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Chronic suppurative otitis media is one of the commonest diseases in the developing countries. The route of infection of ear is predominately through the Eustachian tube orifice. One of the potential risk factor for CSOM is the persistent post nasal discharge associated with chronic sinusitis. This study is done in Tirunelveli Medical College is aimed to document the impact of FESS on the active mucosal type of CSOM. Methods: 80 patients of active mucosal type of CSOM with radiologically proved chronic sinusitis were taken and were subjected to FESS. In those patients 104 ear perforations (including bilateral disease in 24 cases) are categorised into 25 small, 32 medium and 47 large sized perforation depending on the number of quadrants involved. Post-Operative reduction in ear discharge and size of the perforations are noted. Results: Significant changes are seen in ear discharge by 6 weeks. 18 ears out of 104 ears with perforation became dry. 55 and 57 ears became dry post operatively at 3 months and 6 months respectively. Reduction in the size of perforation seen at 3 months and significant changes seen in small and medium perforation categories. 11 out of 25 small sized perforation got closed at 6 months. No significant reduction is seen in large perforation category. Conclusions: There is significant impact of FESS in the outcome of treatment for active mucosal type of CSOM. Significant impact is seen in Small perforations in which more than one third of ears got healed and need not be operated. In others, by making into dry ear the success rate of following ear surgery can be increased.